Psychological Resilience in the Qur'an: A Semantic Analysis of Sakinah and Ath-Thuma'ninah for Mental Health - Mula Saputra, Deden; Sari, Emilia; Ahmadi, Nurul (Civiliza Publishing, 2025)
This article presents a semantic analysis of two Qur’anic concepts related to psychological resilience—sakinah and thuma’ninah—to construct a Qur’an-based model for strengthening mental health. Employing Toshihiko Izutsu’s semantic framework, including etymological, syntagmatic, and paradigmatic analysis, the study demonstrates that these concepts, often treated synonymously in translation, represent distinct psychological states. Sakinah refers to a situational and temporary tranquility bestowed as divine intervention (anzala), functioning as acute psychological stabilization during crises. In contrast, thuma’ninah denotes a stable and enduring tranquility rooted in internal spiritual maturity, developed through sustained dhikr, faith, and mujahadah, and reflected in the formation of the nafs mutma’innah. Based on these findings, the study proposes a three-phase Qur’anic resilience model: adversity, stabilization through sakinah, and transformation through thuma’ninah, which enhances long-term resilience capacity. This model integrates psychological, social, and spiritual dimensions through cognitive reframing, emotional regulation, meaning-making, and post-traumatic spiritual growth within an Islamic worldview. The findings contribute to Islamic psychology and thematic Qur’anic interpretation (tafsir maudhu‘i), offering a theoretical foundation for culturally and spiritually integrated Muslim mental health interventions.